Viability of microwave hybrid sintering process for tungsten carbide cermets - Hammad Thauri, Shahdura (2016)
Microwaves processing ceramics is fast emerging as a new field of ceramic processingand material synthesis, the past year has witnessed significant progress in the aspects ofcommercialization and application of the technology to new areas. Due to that reason,several experiments have been conducted on microwaves heating of ceramics. The aimof the study is to investigate the influence of several binder such as Nickel, Ferum, Chromium and Cobalt to Tungsten Carbide. The study involved the density and hardnessof the sintered samples. The samples were compacted using the instron machine and sintered in microwave hybrid sintering setup for two different of soaking time (10 minutes and 20 minutes). Samples were comparing in terms of the effect of the soaking time on the samples and different binder between Ni-Fe and Ni-Cr, Co-Cr and Co-NiFe that being mix with tungsten carbide. For soaking time of 10 minutes shows a better density and hardness result compared to 20 minutes. In comparison between binder of Nickel and Ferum (Ni-Fe) and Nickel and Chromium (Ni-Cr), binder of Ni and Fe shows a better result compare to Ni and Cr binder. For binder with Cobalt, Nickel and Ferum (Co-Ni-Fe) has an enhanced result compare to binder Co and Cr (Co-Cr). Thus this prove that, Tungsten Carbide (Wc) inserts with several binders can be made using microwave sintering. With the hardness result, insert can be used for machining process to produce tool insert.The composition of powder, density and hardness result may be used depending on specific application.